The Significance of Conceptual Framework towards the Tourism Apps in Influencing Tourist Travel Experience - Qistina Donna, Lee Abdullah; Aimuni Athirah, Latif (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Tourism apps often try to anticipate the needs and demands of travellers to make sure it can make profit for the producer. Sometimes, collaboration between producer of tourism apps and owner of tourism organization such as, accommodation, activities, travel agency and airline play an important role to create effective apps. Apps have many benefits in developing the tourism industry in order to increase economic sector and provide travellers the best travel experience. This paper focuses on the significance of conceptual framework towards the tourism apps in influencing tourist travel experience. The finding of paper also can be used to developing new prototype of tourism apps based on tourist needs. It is to determine the independent variables, dependent variables and moderator for this study. This paper will introduce the best features to be including in tourism apps.